Emergência e institucionalização da sexologia em Portugal : processos, atores e especificidades - Alarcão, Violeta (2017)
Based on Bourdieu's field theory, this article analyzes the emergence and institutionalization of sexology as a science and profession in Portugal, identifying relevant institutions, actors, and professional practices and discussing its relations and specificities. The analysis begins by contextualizing the emergence of modern Western sexology in order to comprehend the Portuguese case in the international sexology context. The second section describes the social, cultural, and institutional factors that have driven the professionalization of sexology. The third section describes the emergence of Portuguese sexology and its principal historical milestones, institutions, and actors. Finally, the article discusses some implications of this process for the role of sexology as a science and profession. The study reveals the dynamics of national and international processes in the field, in the transition from a holistic perspective of sexology to the hegemony of sexual medicine, and sheds light on its mechanisms of legitimation as a transdisciplinary science of sexuality, suggesting future perspectives.